2021
DOI: 10.1002/jmv.27512
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy and safety of current treatment interventions for patients with severe COVID‐19 infection: A network meta‐analysis of randomized controlled trials

Abstract: This study aimed to assess the efficacy and safety of different medications available at present for severe coronavirus disease 2019 (COVID‐19) infection. We searched databases for randomized controlled trials (RCTs) published up to April 30, 2021, with Chinese or English language restriction, of medications recommended for patients (aged 18 years or older) with severe COVID‐19 infection. We extracted data on trials and patient characteristics, and the following primary outcomes: all‐cause mortality (ACM), and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
5
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 55 publications
0
5
1
Order By: Relevance
“…Curiously, our findings differed from our earlier pilot studies, [ 14 , 60 ] which have only indicated 2 effective medications (i.e., IG and methylprednisolone) in the decreased ACM for severe COVID-19 patients. In addition, the CP group showed lower TEAEs than the placebo for severe COVID-19 infection in our earlier NMAs.…”
Section: Discussioncontrasting
confidence: 99%
“…Curiously, our findings differed from our earlier pilot studies, [ 14 , 60 ] which have only indicated 2 effective medications (i.e., IG and methylprednisolone) in the decreased ACM for severe COVID-19 patients. In addition, the CP group showed lower TEAEs than the placebo for severe COVID-19 infection in our earlier NMAs.…”
Section: Discussioncontrasting
confidence: 99%
“…with this interpretation. [67][68][69][70][71] For hydroxychloroquine, a recent collaborative meta-analysis even shows nominally statistically significantly increased mortality. 72 Prior experience from the in-depth analysis of persistent high citations of non-validated papers in other fields may offer us insights on why this situation arose also for COVID-19 treatments.…”
Section: Discussionmentioning
confidence: 99%
“…During the first wave, in-hospital mortality ranged from 21% to 29%, and admission to intensive care units (ICUs) from 14% to 16% [ [1] , [2] , [3] , [4] ]. It should be noted that the efficacy of immunomodulatory and antiviral agents in reducing death or adverse outcome is still debated in COVID-19 patients, mainly when used in advanced phases of the disease [ [5] , [6] , [7] ]. Despite vaccination and spreading of several new variants may have impacted on severity of the disease, caution is required in inferring a reduced severity of COVID-19 infection [ 8 , 9 ].…”
Section: Introductionmentioning
confidence: 99%